Quasi-static analysis of reinforced concrete frame structures using a continuum damage mechanics based model - Rajasankar, J.; Iyer, Nagesh R.; Prasad, A. Meher (Journal of Structural Engineering, 2025)
Quasi-static analysis of reinforced concrete (RC) frame structures carried out using a continuum damage mechanics (CDM) based model proposed by the authors is presented in this paper. The model consists of two components per frame member: i) a non-prismatic elastic member to represent uncracked and sparsely cracked sections and ii) an inelastic hinge to model severely cracked sections and yield response of reinforcement. The model is found to be sufficient to capture the physical changes in a RC frame member such as cracking and yielding under monotonic loading due to imposed lateral displacement. Detailed results of quasi-static analysis of two example RC structures are presented and discussed. First example is a RC column subjected to constant axial load of moderate level w.r.t. its capacity. As second example, a wide two-storey RC plane frame is analysed for its nonlinear response under monotonic lateral load applied by controlling the sway of the frame. In both the examples, variation of base shear with the applied lateral displacement is compared against either experimental values or those available in literature to highlight the performance of the model. Results from present study are found to match well with literature values for the entire load range.